2007
DOI: 10.1681/asn.2006080820
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Nephropathy Developed in Diabetes by (Pro)renin Receptor Blockade

Abstract: Activation of prorenin by (pro)renin receptor stimulates the tissue renin-angiotensin system and plays a significant role in the development of nephropathy in diabetic animals. This study examined whether (pro)renin receptor blockade inhibits the progression of nephropathy that has already developed in diabetic rats. Seventeen-week-old heminephrectomized streptozotocin-induced diabetic rats with an increased urinary protein excretion and a significant glomerulosclerosis had been treated for 12 wk with the (pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
97
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 19 publications
10
97
1
1
Order By: Relevance
“…These findings were recently confirmed by Matavelli et al 14 The direct administration of HRP to the renal cortical interstitium of diabetic rats significantly decreased urinary albumin excretion and the renal production of tumor necrosis factora and interleukin-1b. A similar improvement in nephropathy after HRP treatment was observed in streptozotocin-induced diabetic rats in which nephropathy had already developed 15 and in angiotensin IItype Ia-receptor-deficient mice with streptozotocin-induced diabetes. 16 These latter results indirectly suggested that (P)RR-dependent intracellular signals may also contribute to the development and progression of diabetic nephropathy.…”
Section: Suggestions From Animal Models Of Diabetessupporting
confidence: 69%
“…These findings were recently confirmed by Matavelli et al 14 The direct administration of HRP to the renal cortical interstitium of diabetic rats significantly decreased urinary albumin excretion and the renal production of tumor necrosis factora and interleukin-1b. A similar improvement in nephropathy after HRP treatment was observed in streptozotocin-induced diabetic rats in which nephropathy had already developed 15 and in angiotensin IItype Ia-receptor-deficient mice with streptozotocin-induced diabetes. 16 These latter results indirectly suggested that (P)RR-dependent intracellular signals may also contribute to the development and progression of diabetic nephropathy.…”
Section: Suggestions From Animal Models Of Diabetessupporting
confidence: 69%
“…The same group has shown that administration of handle region peptides to diabetic rats can also cause regression of established diabetic nephropathy. 145 In cultured mesangial cells, it has been suggested that high glucose-induced prorenin upregulation leads to the production of inflammatory cytokines, such as interleukin-1b and cyclooxygenase-2 (Huang and Siragy 146 ). In the retinal vasculature of diabetic mice, Satofuka et al 147 have shown that handle region peptides, also called (P)RR blockers (PRRBs), reduced leukostasis to a greater extent than the AT1-R blocker losartan in wild-type mice and also reduced leukostasis in AT1A receptor gene knockout mice.…”
Section: Role Of Renin-ang Aldosterone System With Emphasis On Aldostmentioning
confidence: 99%
“…This is supported from studies where the excessive non-proteolytic activation of (P)RR-bound prorenin has a major role in diabetic nephropathy and retinopathy, and cardiac fibrosis. 86,88,[100][101][102] As a result of high prorenin level in these diseases, the HRP blocked prorenin binding to the (P)RR (enzymatic activation) and non-proteolytic activation of prorenin by (P)RR. This suggests overexpression of (P)RRs and a predominant role of RAS in these disease conditions.…”
Section: Implication Of (P)rrs In Pathologic Conditionsmentioning
confidence: 99%
“…91,108 In contrast, a predominance of (P)RR expression was noted at the luminal surface of rat kidney collecting duct intercalated cells. 102 The full-length (P)RR, after trafficking to the Golgi, is cleaved by protease furin to liberate a 28 kDa fragment called soluble (P)RR and the 8.9 kDa fragment. 109 Soluble (P)RR is found in both rat and human plasma 109 and human urine.…”
Section: The Cross-talk: (P)rrs and Wnt/fz Signaling Systemmentioning
confidence: 99%